Thermally Annealed Anisotropic Graphene Aerogels and Their Electrically Conductive Epoxy Composites with Excellent Electromagnetic Interference Shielding Efficiencies - Li, Xing-Hua (2017)
Dispersion and spatial distribution of graphene sheets play crucial roles in tailoring mechanical and functional properties of their polymer composites. Anisotropic graphene aerogels (AGAs) with highly aligned graphene networks are prepared by a directional-freezing followed by freeze-drying process and exhibit different microstructures and performances along the axial (freezing direction) and radial (perpendicular to the axial direction) directions. Thermal annealing at 1300 °C significantly enhances the quality of both AGAs and conventional graphene aerogels (GAs). The aligned graphene/epoxy composites show highly anisotropic mechanical and electrical properties and excellent electromagnetic interference (EMI) shielding efficiencies at very low graphene loadings. Compared to the epoxy composite with 0.8 wt % thermally annealed GAs (TGAs) with an EMI shielding effectiveness of 27 dB, the aligned graphene/epoxy composite with 0.8 wt % thermally treated AGAs (TAGAs) has an enhanced EMI shielding effectiveness of 32 dB along the radial direction with a slightly decreased shielding effectiveness of 25 dB along the axial direction. With 0.2 wt % TAGA, its epoxy composite exhibits a shielding effectiveness of 25 dB along the radial direction, which meets the requirement of ∼20 dB for practical EMI shielding applications.